Proses Penyediaan Taman Kota Berdasarkan Fungsi Ruang Terbuka Hijau (Kasus: Taman Kota di Kota Bojonegoro) - Kamilatuzzahroh, Milla; Septiana Hariyani; Siregar, Johannes Parlindungan (RUAS, 2024)
Population density triggers urban density so that urban parks become important infrastructure that has a significant ecological impact while beautifying the environment, entertainment facilities, research, and social spaces. The provision of parks in Bojonegoro City is needed to meet these needs. This study aims to analyze the priority of urban park functions in Bojonegoro based on the function of green open space. The analysis uses the Process Hierarchy Analysis (AHP) method to determine the value of the priority vector of functions and the value of the priority vector on the supporting factors of the provision of urban parks. The results of the study show that the priorities in the process of providing urban parks, both the planning, land provision and blending processes are budget availability (0.859) and socio-cultural functions (0.684). Budget availability allows for routine maintenance, such as garden maintenance, facility repairs, and waste management. The availability of the budget provides a solution for improving the quality of city parks as public RTH in accordance with service standards.